2020
DOI: 10.6008/cbpc2179-6858.2020.007.0040
|View full text |Cite
|
Sign up to set email alerts
|

Classification of radicular biomass and monitoring of litter in Pantanal and Cerrado Mato-Grossense

Abstract: The quantification of root biomass and the assessment of its dynamics in forest ecosystems has been intensified due to its important role in carbon sequestration and storage and the possible consequences under climate change conditions. In general, biomass stocks between and within forest ecosystems are highly variable. It is necessary to study all the different components of vegetation, however, the vast majority of the works found in the literature, address only the biomass of the aerial part of the plants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(23 reference statements)
1
2
0
Order By: Relevance
“…Because P R was not measured for either site during the study period, it was estimated from P W since it was the most consistently measured component and there was enough information from our data and other studies to provide a justifiable estimate of P R . Results from tropical forests indicated that the ratio of P R (coarse and fine) to P W was between 0.80 and 1.25 (Chambers et al, 2004;Malhi et al, 2009);however, Pinto Jr. et al (unpublished) and Taques (2020) found a ratio of 1.96-2.83 for the seasonally flooded Cerrado forest studied here. We chose an average of 1.7 from these studies (Table 1).…”
Section: Inventory Measurementssupporting
confidence: 44%
See 1 more Smart Citation
“…Because P R was not measured for either site during the study period, it was estimated from P W since it was the most consistently measured component and there was enough information from our data and other studies to provide a justifiable estimate of P R . Results from tropical forests indicated that the ratio of P R (coarse and fine) to P W was between 0.80 and 1.25 (Chambers et al, 2004;Malhi et al, 2009);however, Pinto Jr. et al (unpublished) and Taques (2020) found a ratio of 1.96-2.83 for the seasonally flooded Cerrado forest studied here. We chose an average of 1.7 from these studies (Table 1).…”
Section: Inventory Measurementssupporting
confidence: 44%
“…Results from tropical forests indicated that the ratio of P R (coarse and fine) to P W was between 0.80 and 1.25 (Chambers et al., 2004; Malhi et al., 2009); however, Pinto Jr. et al. (unpublished) and Taques (2020) found a ratio of 1.96–2.83 for the seasonally flooded Cerrado forest studied here. We chose an average of 1.7 from these studies (Table 1).…”
Section: Methodsmentioning
confidence: 62%
“…In the three areas analyzed in this study, it was observed that from a depth of 10-20 cm there were decreases in the concentrations of thick roots, which may be due to the Amazonian soils having higher concentrations of nutrients in the more superficial layers, supporting the development of roots in these depths [11]. In similar research, it was observed that the thick roots are spaced in the topsoil, a behavior that may be related to the purpose of each type of root, such as support, nutrient absorption, mineral and water absorption [12]. There were also significant differences in the 0-10 and 10-20 cm shallow depths in relation to other areas for native forest, which may have occurred because the native forest was in balance with the environment and did not suffer anthropic disturbances.…”
Section: Resultsmentioning
confidence: 98%